2017
DOI: 10.2196/publichealth.7741
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Access to HIV Testing and Primary Care Among Migrants Living in Europe: Cross-Sectional Survey

Abstract: BackgroundThere is a heavy and disproportionate burden of human immunodeficiency virus (HIV) infection among migrant communities living in Europe. Despite this, the published evidence related to HIV testing, prevention, and treatment needs for migrants is sparse.ObjectiveThe aim of this study was to identify the factors associated with access to primary care and HIV testing among migrant groups living in Europe.MethodsA Web-based survey (available in 14 languages) was open to all people aged 18 years and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
2
35
0
3
Order By: Relevance
“…[9] However, a Chinese study showed that 20% of Chinese MSM reported prior HIVST usage. [10] The differences between the HIVST usage prevalence 6 between Europe and China might be explained by Europe's legal restrictions on selling HIVST, whereas China has a national policy supporting HIVST. In Europe, only the UK and France have recently approved HIVST for sale (UK: April 2015; France: September 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] However, a Chinese study showed that 20% of Chinese MSM reported prior HIVST usage. [10] The differences between the HIVST usage prevalence 6 between Europe and China might be explained by Europe's legal restrictions on selling HIVST, whereas China has a national policy supporting HIVST. In Europe, only the UK and France have recently approved HIVST for sale (UK: April 2015; France: September 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the aMASE study is provided elsewhere. [5,6] Briefly, the cross-sectional aMASE community survey aimed to identify the structural, cultural, and financial barriers to HIV prevention, diagnosis, and treatment in migrant populations. The community survey was promoted between April 2014 and July 2015 via social marketing and community participatory methods in nine countries (Belgium, France, Germany, Greece, Italy, the Netherlands, Portugal, Spain, and the United Kingdom), although migrants aged 18 or older living in all countries of the World Health Organization (WHO) European area were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Fakoya and colleagues explored factors associated with access to HIV testing and primary care among migrants living in nine European countries—including Spain—in their study recently published in this journal [1]. The authors highlighted the importance of continued HIV knowledge and awareness initiatives aimed at migrant communities.…”
mentioning
confidence: 99%
“…Fakoya and colleagues reported additional individual-level obstacles to HIV prevention and testing such as lack of knowledge about HIV and low perception of risk [1]. The existence of HIV was questioned or denied by a significant number of migrants who participated in our program: 13% (487/3759; 2007-2017), being most of them SSAM.…”
mentioning
confidence: 99%
“…Fakoya and colleagues explored factors associated with access to HIV testing and primary care among migrants living in Europe in their study recently published in this journal 1 . Authors concluded that access is limited by structural determinants such as immigration and healthcare policy, emphasizing that clinicians and other professionals should be aware of these structural barriers and the low perception of HIV risk in migrant groups.…”
mentioning
confidence: 99%